"Lymph node revealing solution: A prospective study on 35 patients with colorectal carcinomas " - "Saleki S; Haeri H " (Acta Medica Iranica, 2002)
Lymph node dissection is of prime importance for accurate staging of colorectal carcinomas. Since a great number of small lymph nodes are missed in the traditional method, several fat clearing solutions have been introduced for easier detection of smaller lymph nodes. In this study we evaluated the efficacy of a new fat clearing solution so-called lymph node revealing solution (LNRS) in colectomy specimens of patients with colorectal carcinoma from year 2000 till 2002, thirty five colectomy specimens with less than 4 metastatic lymph nodes received in the pathology department of IKMC, were selected and re-evaluated using the LNRS. By using this solution 456 additional lymph nodes and 16 more metastatic lymph nodes were detected resulting in upstaging of 3 patients from Duke’s B to C. In all patients categorized as Nx (regional lymph nodes not assessed) by the traditional method, lymph nodes were detected after employment of LNRS. The mean diameter of dissected lymph nodes was significantly smaller than the traditional method (0.268 versus 0.429, P<0.000001). LNRS in comparison with previous solutions is inexpensive, rapid and easy to use. We propose use of this solution in all Duke’s B and patients with no lymph node detection by traditional method.